THE OMBUDSMAN RECONSTRUCTION OF THE REPUBLIC OF INDONESIA IN PROMOTING A RESPONSIVE LEGAL CULTURE - Mansur (Journal of Liberty and International Affairs, 2020)
The aim of this research is to show how the reconstruction of the existing Ombudsman of the Republic of Indonesia influences the promotion of a responsive legal culture in the bureaucratic system. The research methods are normative and empirical, along with the philosophical approach, statute approach, conceptual approach, and direct interview in the field. Concluding the reconstruction of the Ombudsman of the Republic Indonesia to be more ideal through the review of the Law  Number  37 from 2008 regarding the Ombudsman of the Republic of Indonesia including the relation to its institutional authority, and the legal force of the Ombudsman’s recommendations that should be final and binding, so the recommendations have an executorial power.